ANALISIS PERBANDINGAN KINERJA KEUANGAN PERBANKAN BUMN PERIODE 2010 – 2015 - Fazhar Sumantri; Susanti Susanti (Universitas Bina Sarana Informatika, 2016)
BUMN bank is a groups the most influential banks in the Indonesian banking industry. fourth the BUMN Bank namely BRI, Mandiri, BNI, and BTN successively is the largest bank number one, two, four, and Six of a total of 118 banks in Indonesia. The purpose of this study was to analyze the comparisons financial performance BUMN banking consisting of PT Bank Rakyat Indonesia Tbk, PT Bank Mandiri Tbk, PT Bank Negara Indonesia Tbk and PT Bank Tabungan Negara Tbk period 2010 - 2015 using financial ratios. This research is using secondary data, namely in the form of annual financial statements of companies banking BUMN listed on the Indonesia Stock Exchange period 2010 - 2015. Based on the financial performance analyzed include four ratios as measured, this is EPS, PER, PBV and DER, seen that the financial performance PT Bank Rakyat Indonesia Tbk, PT Bank Mandiri Tbk, PT Bank Negara Indonesia Tbk are very dominating and better when compared with PT Bank Tabungan Negara Tbk Testing were performed using One-Way ANOVA test in partially seen that there are differences in the average financial performance of the four companies based EPS, PBV and DER. Whereas in simultaneous, Statistical test results in this study shows the difference in financial performance between the four companies. This result indicates that the portfolio formation that consists of four types of shares will delivers optimal yield considering the fourth these stocks have a different characteristic views of its financial performance. Keywords : Financial Performance, EPS, PER, PBV and DER.